1997
DOI: 10.1080/02673039708720883
|View full text |Cite
|
Sign up to set email alerts
|

Tenure preference and housing strategy: An exploration of Pakistani experiences

Abstract: There is an increasing literature on the exclusion of and difficulties faced by minority ethnic communities in a range of areas, of which housing is one of the most important. But there is relatively little good, recent, qualitative material available, which explores the process of decision‐making-including decisions regarding housing-within minority ethnic families. A missing element, therefore, is the study of action by householders and consequently, the realisation (or otherwise) of preferences and the cumu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 15 publications
1
23
0
Order By: Relevance
“…Also, there is no accepted typology of household preferences in tenure decisions, including those constituting expressions of preferences (Kemeny, 1978;Bowes et al, 1997). Thus we draw a blunt and imprecise distinction between two categories of household preferences: household consumption motives and strategic motives, whilst recognising that tenure decisions are complex cost-bene t trade-offs between these two over time.…”
Section: Household Preferencesmentioning
confidence: 97%
“…Also, there is no accepted typology of household preferences in tenure decisions, including those constituting expressions of preferences (Kemeny, 1978;Bowes et al, 1997). Thus we draw a blunt and imprecise distinction between two categories of household preferences: household consumption motives and strategic motives, whilst recognising that tenure decisions are complex cost-bene t trade-offs between these two over time.…”
Section: Household Preferencesmentioning
confidence: 97%
“…It has been hypothesised that these moves to ethnic concentration neighbourhoods are (partly) motivated by the desire to live in areas with others who have common life experiences and by the availability of ethnic specific services (see Bowes et al, 1997). Other studies have emphasized the impact of socio-economic differences between ethnic and non-ethnic groups (e.g.…”
Section: Of Benefits (Hypothesis 1)mentioning
confidence: 99%
“…Various researchers have shown that fear of discrimination or harassment prevented ethnic or racial minorities from moving to better (and 'whiter') neighbourhoods (Bowes et al, 1997;Hanhӧrster, 2013;Phillips et al, 2007). Also, research in the Netherlands shows that ethnic minorities do not want to live in neighbourhoods with mainly native Dutch inhabitants because they are afraid that they will not be accepted there or will not be able to relate to their neighbours (Kullberg et al, 2009).…”
Section: Literature Review and Backgroundmentioning
confidence: 99%